Diversity and Biomineralization Potential of the Epilithic Bacterial Communities Inhabiting the Oldest Public Stone Monument of Cluj-Napoca (Transylvania, Romania) - Andrei, Adrian-Ştefan; Păuşan, Manuela R.; Tămaş, Tudor; Har, Nicolae; Barbu-Tudoran, Lucian; Leopold, Nicolae; Banciu, Horia L. (Frontiers in Microbiology, 2017)
In this study, we investigated the biomineralization potential and diversity of the epilithic bacterial communities dwelling on the limestone statue of Saint Donatus, the oldest public monument of Cluj-Napoca city (Transylvania region, NW Romania). Their spatial distribution, together with phylogenetic and metabolic diversity, as well as their capacity to precipitate calcium carbonate was evaluated by combining molecular and phenotypic fingerprinting methods with X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and scanning electron-microscopy (SEM) analyses. The results of real-time quantitative PCR, molecular fingerprinting and community-level physiological profiling showed that diverse and abundant bacterial assemblages that differ in relation to their collection site colonized the statue. The cultivation and molecular identification procedures used allowed the characterization of seventy-nine bacterial isolates belonging to Proteobacteria (73.4%), Firmicutes (19%) and Actinobacteria (7.6%). Amongst them, the twenty-two strains identified as being capable of calcium carbonate precipitation were found to belong mostly to Bacillus and Pseudomonas genera. We found that bacteria acted as nucleation sites, inducing the formation of nanoscale aggregates that were shown to be principally composed of vaterite. Furthermore, we expanded the current knowledge of culturable diversity of carbonatogenic bacteria by providing unprecedented evidence for biogenic vaterite/calcite formation mediated by: Pseudomonas synxantha, Pseudomonas graminis, Brevibacterium iodinium, Streptomyces albidoflavus and Stenotrophomonas chelatiphaga. Overall, this study highlights the need to evaluate the carbonatogenetic potential of all the bacterial communities present on stone artwork prior to designing an efficient conservation treatment based on biomineralization.